PENGENALAN APLIKASI AKUNTANSI UKM BERBASIS HANDPHONE PADA PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) BATIK CIREBON - Lailah Fujianti; Tyahya Whisnu Hendratni (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Micro, Small and Medium Enterprises (MSMEs) Cirebon Batik has a significant role in the development of the National Economy. MSMEs Batik Cirebon is a growing and developing economy based among the people who has the potential to be upgraded the backbone of the country's economy, because batik is one of Indonesia's proud garment products. Cirebon Batik MSMEs has experienced financial problems including financial management. Education is one way to make MSMEs aware of the importance of financial management. Therefore, our service is to provide education on the introduction of the Mobile-based Accounting Application for MSMEs in Batik Cirebon MSMEs which aims to facilitate and accelerate the preparation of financial statements.Keywords: MSMEs Accounting Application, Mobile Based Application, Education, MSMEs Batik Cirebon.